Implementation of the Relationship between Christ and the Congregation Based on Ephesians 5:22-6:4 in the Servants of God Synod of the Christian Ministry Church - Putra, Abraham Firman; Daliman, Muner; Suparti, Hana; Sugiyarto, Kristian Handoyo (Technium Social Sciences Journal, 2023)
Ephesians 5:21-33 teaches that marriage is a picture of Christ's relationship with the church. Christ is the Head and the Church is the body. Such is marriage, where the husband acts as the head and the wife as the body. However, this is different from the fact that among the servants of God, the Indonesian Christian Service Church Synod, where there are still husbands and wives who do not understand their roles, causing problems in marriage. This problem specifically occurs among the servants of God at the Synod of the Indonesian Christian Ministry Church. That's why this article was conducted to determine the level of understanding of the congregation in implementing the relationship between Christ and the church based on Ephesians 5:22-6:4. To find the intended purpose, this research was conducted using quantitative research methods. The research results obtained are that the dominant background category determines the Implementation of the Relationship between Christ and the Congregation Based on Ephesians 5:22-6:4 in the Servants of the Lord Jesus Synod Church Christian service is education, this is the same as the hypothesis proposed. The results of the analysis using Classification and regression trees (CRT) show that educational background is the most dominant background category in shaping the Implementation of the Relationship between Christ and the Congregation Based on Ephesians 5:22-6:4 in the Servants of God Synod of the Christian Ministry Church (Y) . From the suragates table it is known that educational background is able to improve by 64,949 points from the condition of the Implementation of Christ's Relationship with the Congregation Based on Ephesians 5:22-6: 4 in the Servants of God Synod of the Christian Ministry Church (Y). As well as from the importance table it is known that background employment status is affirmed by 100% of respondents with a score of 75.187 points